Similarity analysis of bioconvection of unsteady nonhomogeneous hybrid nanofluids influenced by motile microorganisms - Mabrouk, Samah Mohamed; İnç, Mustafa; Rashed, Ahmed Saad; Akgul, Ali (Springer, 2024)
Motile bacteria in hybrid nanofluids cause bioconvection. Bacillus cereus, Pseudomonas viscosa, Bacillus brevis, Salmonella typhimurium, and Pseudomonas fluorescens were used to evaluate their effect and dispersion in the hybrid nanofluid. Using similarity analysis, a two-phase model for mixed bioconvection magnetohydrodynamic flow was developed using hybrid nanoparticles of Al2O3 and Cu (Cu-Al2O3/water). The parametric investigation, covering the magnetic parameter, permeability coefficient, nanoparticle shape factor, temperature ratio, radiation parameter, nanoparticle fraction ratio, Brownian parameter, thermophoresis parameter, motile bacteria diffusivity, chemotaxis parameter, and Nusselt, Reynold, Prandtl, Sherwood numbers, as well as the number of motile microorganisms', showed significant outcomes. Velocity and shear stresses are sensitive to M, Pr, and k(p)(*). Magnetic, radiation, and chemotaxis factors impact bacterial density. The hybrid nanofluid velocity decreases when the magnetic parameter, M, Prandtl number Pr increases, while it increases with the increasing of porosity coefficient, k(p)(*), and the hybrid nanoparticle ratio N-f. The temperature distribution decreases with the increasing of Prandtl number and N-f. Increasing temperature differential and bacterium diffusivity increases bacterial aggregation.
Keywords: Hybrid nanofluids; Bioconvection; Agglomeration; Brownian motion parameter